The Gut Bacteria Dysbiosis Contributes to Chronic Graft-Versus-Host Disease Associated With a Treg/Th1 Ratio Imbalance - Wang, Yulian; Huang, Lisi; Huang, Tian; Geng, Suxia; Chen, Xiaomei; Huang, Xin; Lai, Peilong; Du, Xin; Weng, Jianyu (Frontiers in Microbiology, 2022)
Introduction Dysbiosis of gut bacteria has been discovered in a large number of autoimmune diseases. However, the influence of the gut bacteria in the mice model of chronic sclerodermatous graft-versus-host disease (Scl-GVHD), a disease that resembles an autoimmune disease characterized by chronic inflammation of multiple organs, such as skin, remains elusive. Here, we explore the role of gut bacteria in an Scl-cGVHD mice model. Methods We established a mouse model of Scl-cGVHD, collected fecal flora, analyzed the composition, and diversity of intestinal flora using 16S rDNA amplicon sequencing, and detected the proportion of Treg and Th1 cells in splenocytes of Scl-cGVHD mice. To verify the immunoregulatory effect of Scl-cGVHD intestinal flora, we prepared bacterial extracts, co-cultured with splenocytes in vitro, and used flow cytometry to detect T cell differentiation and cytokine secretion. Results By examining T-cell differentiation in splenocytes of cGVHD mice, we found that Treg cells were significantly reduced (15.27 ± 0.23 vs. 12.23 ± 0.47, p = 0.0045) and Th1 cells were increased (1.54 ± 0.18 vs. 6.68 ± 0.80, p = 0.0034) in cGVHD mice. Significant differences were observed in the composition and diversity of the gut bacteria in mice with Scl-cGVHD versus without GVHD. Analysis of mice fecal bacteria samples (n = 10, 5 Scl-cGVHD and 5 Non-GVHD) showed significant separation [R = 0.732, p = 0.015, non-parametric analysis (ANOSIM)] in Scl-cGVHD and non-GVHD mice. The abundance of the family and genus Ruminococcaceae bacteria decreased and the family Lachnospiraceae and limited to the species Lachnospiraceae_bacterium_DW17 increased in Scl-cGVHD mice. In vitro results of the cellular level study suggest that the bacteria extracts of gut microbiota from Scl-cGVHD mice modulated the splenic T cells toward differentiation into CD4+IFN-γ+ Th1 cells (14.37 ± 0.32 vs. 10.40 ± 2.19, p = 0.036), and the percentage of CD4+CD25+Foxp3+ Tregs decreased (6.36 ± 0.39 vs. 8.66 ± 0.07, p = 0.001) compared with the non-GVHD mice. In addition, the secretion of proinflammatory interferon- γ (IFN-γ) cytokine in the supplement of cellular culture was increased (4,898.58 ± 235.82 vs. 4,347.87 ± 220.02 pg/ml, p = 0.042) in the mice model of the Scl-cGVHD group, but anti-inflammatory interleukin (IL)-10 decreased (7,636.57 ± 608.05 vs. 9,563.56 ± 603.34 pg/ml, p = 0.018). Conclusion Our data showed the different composition and diversity of gut bacteria in the Scl-cGVHD mice. The dysbiosis of gut bacteria may regulate the differentiation ratio of Treg and Th1 cells, which was associated with Scl-cGVHD.